Isolation of ?-Sitosterodiglucoside and ?-Sitsteryl Arabinoside from Rhizomes Alpinia galanga - B. Jaju, Shivkanya; Indurwade, N.H.; Sakarkar, D.M.; Ali, M.; Fuloria, N.K. (Asian Journal of Chemistry, 2010)
This paper reports β-sitosterodiglucoside (AG 7) and β-sitsteryl arabinoside (AG 8), two constituents isolated from Alpinia galanga are characterized on the basis their spectral value.